2014
DOI: 10.1002/ijch.201400080
|View full text |Cite
|
Sign up to set email alerts
|

P450BM3‐Axial Mutations: A Gateway to Non‐Natural Reactivity

Abstract: Enzymes capable of catalyzing non‐natural reactions have the potential to alter the way relevant molecules are prepared on‐scale. Efforts to this end have largely focused on combining non‐natural cofactors with proteins lacking catalytic function to obtain non‐natural reactivity. An alternative approach is to utilize a native cofactor to catalyze non‐natural reactions. Recently, our group demonstrated that heme‐containing cytochrome P450s are able to catalyze the highly selective cyclopropanation of alkenes. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
1
24
0
1
Order By: Relevance
“…To combine the favorable qualities of enzymes with the diverse reactivity of synthetic transition-metal catalysts, abiological transition-metal centers or cofactors have been incorporated into native proteins. The resulting artificial metalloenzymes catalyze classes of reactions for which there is no known enzyme (abiological transformations) (3,4).…”
mentioning
confidence: 99%
“…To combine the favorable qualities of enzymes with the diverse reactivity of synthetic transition-metal catalysts, abiological transition-metal centers or cofactors have been incorporated into native proteins. The resulting artificial metalloenzymes catalyze classes of reactions for which there is no known enzyme (abiological transformations) (3,4).…”
mentioning
confidence: 99%
“…[14] Arnold was interested in exploring the ability of cytochrome P450s to catalyze carbene transfer reactions. [15] In as eminal report, P450 BM3 was shown to be an effective catalyst for the cyclopropanation of styrenes when using ethyl diazoacetate (EDA) as ac arbene source under anaerobic conditions,t hereby providing product with low conversion and selectivity (TTN 5; TTN = total turnover number). [16] A single mutation of the conserved distal threonine (T268), hypothesized to facilitate proton transfer in the natural reactivity,toalanine (P450 BM3 -T268A) enabled trans-selective cyclopropanation in high yield and enantioselectivity (Figure 1, top).…”
Section: Cytochrome P450smentioning
confidence: 98%
“…The groups of Arnold and Fasan have now demonstrated that formal Fe IV –carbenoid and Fe IV –nitrenoid compounds, which are isoelectronic to Fe IV –oxo, are generated in various heme proteins and insert into C–H, N–H, and S–H bonds. These C–C, C–N, and C–S bond‐forming reactions catalyzed by designed metalloenzymes are valuable, because they proceed in water, at room temperature, and are very stereoselective; this is difficult to achieve with chemical catalysts 1820. The following carbene and nitrene transfer reactions have been described to be catalyzed by the iron porphyrin proteins: (1) carbene transfer: cyclopropanation,2126 amination,27,28 sulfidation;29 (2) nitrene transfer: sulfamination,3033 sulfimination,34 oxazolidinone formation 35…”
Section: New Reactionsmentioning
confidence: 99%